Operationalizing a Multi-Sectoral Approach for the Reduction of Stunting in Indonesia : An Application Using the 2007 and 2013 Riskesdas - World Bank (World Bank, Washington, DC, 2017)
Stunting is a widespread and persistent condition in Indonesia with more than one-third of young children being stunted. The national stunting rate for under five-year-olds increased slightly from 3.8 percent in 2007 to 37.2 percent in 2013, based on official stunting rates reported by the Ministry of Health of the Government of Indonesia. During the same time period, the percentage of population in poverty reduced from 16. Percent to 11.4 percent (World Bank), suggesting that the increased purchasing power did not translate to better nutritional outcomes for children.